A Cloud-Based Integrated Management Model: Driving Operational Efficiency and Financial Accountability in Teacher Education Programs - Yuli Soesetio; Muhammad Fuad; Sigit Permansah; Darmawan Satyananda; Bima Wahyu Pratama; Ervira Mayasari; Lifa Rosiana Putri (SAFE-Network, 2026)
The management of the Teacher Professional Education (PPG) program involves a highly complex administrative and financial ecosystem, making it susceptible to bureaucratic inefficiency and information fragmentation among implementing divisions. This study aims to develop and implement a cloud-based Integrated Management Model utilizing digital job order cards to accelerate operational efficiency and strengthen reporting accountability. Adopting a participatory managerial innovation design, this research reengineers conventional workflows into a cohesive digital ecosystem. Data were collected through methodological triangulation, encompassing operational observations, system log extraction, and in-depth interviews with university leadership, administrative staff, and the finance division at the Graduate School of Universitas Negeri Malang. The implementation results demonstrate that system integration successfully curtailed clerical redundancy substantially and accelerated the fund availability verification process by up to 50%. The establishment of a centralized database created a single source of truth that effectively eliminated information asymmetry across units. Furthermore, the system automatically generated a digital audit trail ensuring every budget absorption was recorded transparently, thereby minimizing the probability of reporting revisions. In conclusion, managerial transformation through governance digitalization proves essential in realizing good governance principles. This integrated model serves not merely as a tactical solution for PPG operational effectiveness but also presents a highly scalable strategic prototype replicable across various other academic programs.